1997
DOI: 10.1042/bj3210503
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of inactivation of myeloperoxidase by 4-aminobenzoic acid hydrazide

Abstract: Hypochlorous acid is the most powerful oxidant generated by neutrophils and is likely to contribute to the damage mediated by these inflammatory cells. The haem enzyme myeloperoxidase catalyses its production from hydrogen peroxide and chloride. 4-Aminobenzoic acid hydrazide (ABAH) is a potent inhibitor of hypochlorous acid production. In this investigation we show that, in the presence of hydrogen peroxide, ABAH irreversibly inactivates myeloperoxidase. ABAH was oxidized by myeloperoxidase, and kinetic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
182
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(197 citation statements)
references
References 34 publications
14
182
1
Order By: Relevance
“…ABAH (42) and azide (43) are both inhibitors of MPO, and both attenuated DMPO-MPO adduct formation. Ascorbate is a substrate and also a reductant in that MPO/H 2 O 2 can oxidize ascorbate, but, perhaps more importantly, ascorbate can rapidly reduce many radical intermediates formed by peroxidases (44).…”
Section: Discussionmentioning
confidence: 99%
“…ABAH (42) and azide (43) are both inhibitors of MPO, and both attenuated DMPO-MPO adduct formation. Ascorbate is a substrate and also a reductant in that MPO/H 2 O 2 can oxidize ascorbate, but, perhaps more importantly, ascorbate can rapidly reduce many radical intermediates formed by peroxidases (44).…”
Section: Discussionmentioning
confidence: 99%
“…ABAH (45) and azide (46) are both inhibitors of MPO, and both attenuated DMPO-MPO adduct formation. Ascorbate is a substrate in that MPO/H 2 O 2 can oxidize ascorbate, but perhaps more importantly, ascorbate can rapidly reduce many radical intermediates formed by peroxidases (47).…”
Section: Discussionmentioning
confidence: 99%
“…As mechanism-based inhibitors of peroxidases have been proposed to form reactive free radical intermediates that bind to the heme active site and inhibit enzyme activity (43)(44)(45)(46), we assayed the remaining peroxidase activity after incubation with PA. However, we found no inhibition of MPO peroxidase activity after treatment with PA (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…There has been considerable interest in the development of therapeutically useful MPO inhibitors. A previous study showed that 4-ABAH irreversibly inhibits hypochlorous acid production as a suicide substrate of MPO 7 . A means of monitoring MPO activity under in vivo conditions should help establish the relationship between MPO induction and pathological progression and facilitate preclinical evaluation of MPO inhibitors.…”
mentioning
confidence: 99%